Design and parameters optimization of the curved sieve for an air suction jujube harvester - Bai, Shenghe; Yuan, Yanwei; Niu, Kang; Zhou, Liming; Zhao, Bo; Wei, Liguo; Liu, Lijing; Zhang, Xuejun (International Journal of Agricultural and Biological Engineering, 2024)
In order to improve the screening performance and cleaning effect of the jujube harvesting machinery cleaningdevice, a vibrating curved screen device was designed in this study. By analyzing the structure mechanism of the curved sievebody, it was obtained that the arc-shaped mesh hole spacing S was 15-25 mm and the curved mesh hole curvature U was 90°-150°. By exploring the movement state and stress of jujube and impurities on the curved sieve body, it was determined that thehorizontal spacing L of the curved layer sieve was 30 mm and the vertical spacing H was 45-65 mm. Taking the verticalspacing H of the curved layer sieve, the curvature U of the curved mesh hole, and the spacing S of the curved mesh hole as theexperimental factors, considering the screening efficiency α and the impurity content β of the jujube as the response values, thethree-factor three-level quadratic regression orthogonal experiment was designed, establishing the regression mathematicalmodel of each factor and response value, and the multiple target optimization algorithm of Design-expert software was used tooptimize various factors. The results showed that the influence factors on the screening efficiency were in the descending orderas: the arc screen spacing, the vertical spacing of the curved layer screen, and the curved screen hole curvature; The significantfactors affecting the impurity content of jujube were in the descending order as: the arc screen spacing, the curved screen holecurvature, and the vertical spacing of the curved layer screen. The experimental results were verified by the optimizedcombination of parameters: when the vertical spacing H of the curved layer screen was 65 mm, the curved screen holecurvature U was 110°, and the arc screen spacing S was 23 mm, the average screening efficiency α in the test was 91.09%. Therelative error between the experimental verification value and the theoretical optimization value was 1.36%, which was lessthan 5%. The impurity content of jujube β in the test was 1.02%. The relative error between the experimental verification valueand the theoretical optimization value was 2.00%, which was also less than 5%. The test results can provide a reference for theresearch and optimization of the subsequent air-suction-type jujube harvester cleaning device. Keywords: jujube harvesting, cleaning device, curved sieve, sieve structure, conveying pipe, mathematical model DOI: 10.25165/j.ijabe.20241702.7818 Citation: Bai S H, Yuan Y W, Niu K, Zhou L M, Zhao B, Wei L G, et al. Design and parameters optimization of the curved sieve for an air suction jujube harvester. Int J Agric & Biol Eng, 2024; 17(2): 132–139.